BRITISH AND AMERICAN EDUCATIONAL SYSTEMS APPLICATION IN UKRAINE - Malina-Gilchenko, K.A.; Gilchenko, R.A. (Proceedings of National Aviation University (archive), 2005)
Considered are the complex issues of reforms in the field of pre-school, school and higher education of Ukraine. Taking into consideration the modern educational tendencies and the desire of Ukraine for eurointegration, the authors of the article believe, that the future of the education of Ukraine is closely bound to the harmonious conjunction of the best traditions of classical Soviet and Ukrainian schools, and achievements of British and American educational models.